Robust, sustainable cellulose composite aerogels with outstanding flame retardancy and thermal insulation. (15th February 2020) - Luo, Xiaolei; Shen, Junyan; Ma, Yanan; Liu, Lin; Meng, Ranju; Yao, Juming
Graphical abstract: Highlights: Cellulose aerogels were prepared by incorporating LDH as green nanofiller. A novel strategy to exfoliate LDH into nanosheets. The cellulose aerogels exhibited dramatically increased mechanical properties. Outstanding flame retardancy and smoke suppression performance were achieved Enhancement mechanisms of mechanical and flame retardant were well investigated. Abstract: Robust and sustainable cellulose composite aerogels were prepared by incorporating MgAl-layered double hydroxide (MgAl-LDH) as green nanofillers and flame retardants. Two series of aerogels combining MgAl-CO3 LDH (MA-C) and MgAl-H2 PO4 LDH (MA-P) were achieved, in which both MA-C and MA-P were uniformly dispersed in cellulose substances. The cellulose composite aerogels with 1.8 wt% of MA-C (denoted as CAC) and MA-P (denoted as CAP) displayed excellent mechanical properties, increased by 2.6 and 2.8 times compared with neat cellulose aerogels (CA), respectively. The peak of heat release rate (PHRR) of CAC and CAP reduced by 41 % and 50 % compared with the neat one, respectively, demonstrating the outstanding flame retardancy. The reduction in smoke production ratio (SPR) was 79 % for CAC and 75 % for CAP, respectively, indicating enhanced smoke suppression performance. Therefore, the high performance flame-retardant cellulose composite aerogels exhibit an application prospect in green advanced engineering field.